Peran Perpustakaan Umum Bagi Masyarakat : Studi Kasus Perpustakaan Umum di Bali - Luh Putu Sri Ariyani; I Gusti Made Arya Suta Wirawan (Universitas Pendidikan Ganesha, 2017)
AbstrakThis study aims to (1) identify problems faced by public libraries in its development, (2) identify public library management system in Bali; (3) identify various programs developed in public libraries. This research is conducted by using qualitative research methods so that the target of this study is not on measurement, but on the understanding of social phenomena from the perspective of the participants or according to the perspective of emik. The results show that the common problems faced by public libraries are as follows: library buildings that are less representative; Lack of human resources / librarians; lack of library operational funds; job placement uncertainty. Public library management system is almost the same in every library, which distinguishes the allocation of funds disbursed by local governments. While the programs developed in public libraries include: mobile library; story telling; cross-service collection; rare library search; and special services. Keywords: public library, management, flagship program